KAJIAN PSIKOANALISIS DAN RELIGIUSITAS DALAM NOVEL KETIKA TUHAN JATUH CINTA KARYA WAHYU SUJANI - Herlia; Missriani (Universitas PGRI Palembang, 2022)
Therapy is a brain research strategy used to study the mental aspects of character in scientific work, and religiosity is a perspective related to religion. The question in this research is how is the psychoanalysis and religiosity of the characters in the novel When God Falls in Cherish by Wahyu Sujani.The investigative method used can be a definite strategy and the approach used can be a spiritual approach. The source of this research is the 442-page novel When God Falls in Adore by Wahyu Sujani which was first published in 2011. t 20cm x 14cm and distributed wildly by Diva Press, Yogyakarta. It can be concluded based on the results of research and discourse that the identity of the characters in the novel includes the desire to eventually become successful, the desire to study at state universities, and the desire not to skip classes. Opportunity, desire to mindfully shape Iruru, Fikri's desire to become an evangelist, etc., wanting to take Angrayan, welcoming friends home, and so on. en Trustees, acting as trustees, providing support, dealing with religion, etc. It's in God's book. About caregivers, requests and forgiveness, kindness to caregivers, welcome and response, patient comfort.